Memorandum of understanding within the UiTM context - Khalid, Azlena (Pejabat Penasihat Undang-Undang, 2015)
Memorandums of Understanding (MoUs) in UiTM record parties’ willingness to cooperate and are generally non-legally binding. Their format follows guidelines from the Attorney General’s Chambers of Malaysia and resembles standard contracts, though the provisions are representational rather than enforceable.